A new subspecies of Thaumantis hainana (Crowley, 1900) from Guizhou province, southwest region of China (Lepidoptera: Nymphalidae) - Xue-jian Wang; Song-yun Lang (SHILAP, 2023)
In this paper, the Thaumantis diores Doubleday, 1845-complex, including T. diores Doubleday, 1845 and T. hainana (Crowley, 1900), is studied, and a new subspecies, T. hainana libodiores Lang & Wang, ssp. nov., is described from Guizhou province, S.W. China.